THE EFFECTIVENESS OF STATIC ELECTRIC VIRTUAL REALITY PANDEMIC LEARNING MEDIA TO INCREASE STUDENT LEARNING MOTIVATION - Rif’atul Mahmudah (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
q